The Effect of Price, Product Quality and Service Quality Analysis at Jelly Potter Palsigunung Branch - Dewi Panca Lestari Wijaya (Universitas Mercu Buana, 2023)
This study aims to analyze the effect of Price, Product Quality and Service Quality on customer satisfaction at Jelly Potter Palsigunung branch. The population of this research is the customers at Jelly Potter Palsigunung branch. The sample were 100 customers, calculated based on the Djarwanto and Subagyo formula. Sampling method using accidental sampling. This research used survey methods, with the research instrument is a questionnaire. The data analysis method uses Statistical Program Social Scientist (SPSS) version 20. The result showed that price has a positive and significant effect on customer satisfaction, product quality has a positive and significant effect on customer satisfaction, and Service Quality has a positive and significant effect on customer satisfaction.